Effect of different liver biopsy needle track management on Yttrium-90 selective internal radiation therapy on liver cancer - Zhenyuan XU; Xue LIU; Shuqun SHEN; Zhijia XU; Changkai LI; Yefa YANG (Zhongguo Linchuang Yixue)
ObjectiveTo explore the effect of different needle track management on Yttrium-90 microsphere selective internal radiation therapy (90Y-SIRT) on liver cancer after liver biopsy. MethodsA retrospective analysis was conducted on the clinical data of 21 patients with liver cancer who underwent Technetium-99m-macroaggregated albumin (99mTc-MAA) evaluation and 90Y-SIRT after liver biopsy from June 2023 to December 2024. The methods of needle track management, hepatic arteriovenous shunting, and lung shunt fraction (LSF) were recorded. The occurrence of hepatic arteriovenous fistula (HAVF), as well as the corresponding countermeasures were analyzed. ResultsAmong the 21 liver cancer patients, 7 cases (medical glue group) underwent embolization of the needle tract with medical glue (N-butyl 2-cyanoacrylate [NBCA]) immediately after biopsy, and no significant HAVF was observed during the 99mTc-MAA tests; 14 cases (non-medical glue group) were treated with delayed needle extraction or gelatin sponge particle blocking after biopsy, among which 7 cases developed significant HAVF, and the fistulas were treated with NBCA. The LSF of the medical glue group was significantly lower than that of the non-medical glue group ([7.06±2.33] % vs [12.43±7.73] %, P＝0.037). All 21 patients successfully completed 90Y-SIRT. ConclusionsLiver biopsy may affect 90Y-SIRT by causing iatrogenic HAVF. Immediate NBCA-embolization of the needle tract after biopsy or timely NBCA-embolization of fistulas during 99mTc-MAA tests may reduce the impact.